Optimisation of oleanolic acid extraction from pokok bunga tahi ayam' (Lantana Camara) roots by methanol-ethyl acetate solvent using resronse surface methodology / Rasimah Mahat - Mahat, Rasimah (Faculty of Applied Sciences, 2009)
Lantana camara is an ornamental plant used in tradition medicine for the treatment of various diseases. The roots of L. camara is a rich of oleanolic acid which has shown anti-inflammatory, hepatoprotective, antitumor, antioxidant and antihyperliperdemic activity. Optimisation of various extraction parameters using response surface methodology (RSM) was performed to asses maximum yield of oleanolic acid from L.camara roots. MINITAB software version 14 was used to identify the significant effect of various extraction parameters such as concentration of solvent-solid ratio (mL:g), extraction temperature and extraction time. Among the three variables tested, concentration of solvent-solid ratio (mL:g) and extraction temperature were found to have significant effect on oleanolic acid extraction. Optimum level of the significant variables were determined by using central composite design. The optimum condition for extraction of oleanolic acid was found at 30 mL/g of concentration of solvent-solid ratio, 60QC of extraction temperature and 30 minutesof extraction time. At optimum extraction parameters, the optimum yield of oleanolic acid obtained experimentally (1.36609 %) was found to be very close to its predicted value determined by (1.2915%) MINITAB software version 14.